Actual problems of formation of rational state system of regulation of maintenance of airworthiness of aircrafts in Ukraine - Орлов, A. B. (Proceedings of National Aviation University (archive), 1999)
Considered is the structure of state regulation system of airworthiness and the problem of synthesis of rational regulation for specific conditions of distribution of regulation between three mandatory and interconnected directions of regulation